1968
DOI: 10.1002/pol.1968.150060508
|View full text |Cite
|
Sign up to set email alerts
|

Studies of polymers from cyclic dienes. IV. Determination of the structure of polycyclopentadiene

Abstract: Abstract3,4‐ and 3,5‐Dimethylcyclopentenes were prepared as model compounds of the structural unit in polycyclopentadiene. These two isomers give characteristic NMR spectra. The assignment based on the 60 Mc./sec. spectrum was further confirmed by decoupling experiments on the 100 Mc./sec. spectrum of 3,5‐dimethylcyclopentene. By comparing the NMR spectra of these compounds with that of polycyclopentadiene methods were developed for estimating the polymer structure from the relative peak area of the methine–me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

1969
1969
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 3 publications
1
30
1
Order By: Relevance
“…Consequently, the cationic polymerization of I V seems likely t o proceed according to the scheme (9). The enhanced tendency of this monomer to undergo cationic polymerization is contrary t o our earlier presumption and may be attributed to the increase in the x-electron density of the monomer or to the increase in the stability of the propagating cation or t o both.…”
Section: Cationic Polymerizability Of 13-dimethylcyclopentadienecontrasting
confidence: 56%
See 2 more Smart Citations
“…Consequently, the cationic polymerization of I V seems likely t o proceed according to the scheme (9). The enhanced tendency of this monomer to undergo cationic polymerization is contrary t o our earlier presumption and may be attributed to the increase in the x-electron density of the monomer or to the increase in the stability of the propagating cation or t o both.…”
Section: Cationic Polymerizability Of 13-dimethylcyclopentadienecontrasting
confidence: 56%
“…Of the two carbonium ions IX and X, however, X seems t o be predominant on the basis of the following considerations. Our previous study on the cationic polymerization of 1-methylcyclopentadiene (XII) showed that this monomer reacted at the 4-position to yield XIII, as shown in scheme (11)2), which is similar t o the formation of X in reaction (9). In fact, an NMR spectrum of the monomer in concentrated sulphuric acid indicated the formation of cation XI (ref.…”
Section: Cationic Polymerizability Of 13-dimethylcyclopentadienementioning
confidence: 84%
See 1 more Smart Citation
“…The latter region consisted of three well‐resolved parts, that is, 1.4–1.8 (A), 1.8–2.2 (B), and 2.2–2.8 ppm (C). The 1,2‐ and 1,4‐contents could be calculated from their integrated signal intensities by the literature methods 19. The observed D/(A + B + C) ratios for all the polyCPDs polymerized at low temperatures were close to 0.5, and this indicated the absence of side reactions under our conditions with MAO as a catalyst.…”
Section: Resultsmentioning
confidence: 75%
“…Remarkable studies on CPD polymerization were carried out by Sigwalt et al15, 16 using as a catalyst the stable carbon cation salt Ph 3 C + SbCl 6 to obtain quite high molecular weight polyCPD, which was entirely soluble in the solvent methylene chloride. Important kinetic studies on CPD polymerization were carried out by Imanishi and coworkers17, 18 using the binary catalysts TiCl 4 /CCl 3 COOH, SnCl 4 /CCl 3 COOH, and BF 3 ·Et 2 O. Aso and coworkers19–23 investigated in detail the microstructure of polyCPD obtained with cationic initiators. Interesting results on CPD polymerization in the presence of several cationic initiators were reported by Schmidt and Kolb 24.…”
Section: Introductionmentioning
confidence: 99%